Meningitic Escherichia coli-Induced Interleukin-17A Facilitates Blood–Brain Barrier Disruption via Inhibiting Proteinase 3/Protease-Activated Receptor 2 Axis - Xu, Bojie; Chen, Jiaqi; Fu, Jiyang; Yang, Ruicheng; Yang, Bo; Huo, Dong; Tan, Chen; Chen, Huanchun; Wang, Xiangru (Frontiers in Cellular Neuroscience, 2022)
Bacterial meningitis is a life-threatening infectious disease with high morbidity and mortality worldwide, among which meningitic Escherichia coli is a common gram-negative pathogenic bacterium causing meningitis. It can penetrate the blood−brain barrier (BBB), invoke local inflammatory responses and consequently disrupt the integrity of the BBB. Interleukine-17A (IL-17A) is recognized as a pro-inflammatory cytokine that is released during meningitic E. coli infection. It has been reported that IL-17A is involved in several pathological tissue injuries. However, the function of IL-17A in BBB breakdown remains rarely discussed. Here, our study found that E. coli-induced IL-17A led to the degradation of tight junction proteins (TJs) and adherens junction proteins (AJs) in human brain microvascular endothelial cells (hBMECs) through inhibiting protease proteinase 3 (PRTN3)/protease-activated receptor 2 (PAR-2) axis, thus increasing the permeability of BBB. In summary, this study uncovered the involvement of IL-17A in regulating BBB integrity and proposed a novel regulatory mechanism, which could be potential therapeutic targets of E. coli meningitis.